Peran Tokoh Agama dalam Meningkatkan Spiritualitas Masyarakat di Kabupaten Bojonegoro - Anjarahmi, Marissa Dwi; Alamin, Taufik (Journal of Islamic and Social Studies, 2023)
Religion is seen as an instrument for understanding the world. Religion can be a backbone for people in behaving in social life. Religion also has an important role in regulating the relationship between humans and their God, humans and other humans, and humans and their environment. The presence of religion makes people able to face problems in human life. This research method is a qualitative method with a case study approach by means of observation, interviews and documentation. By taking 5 subjects to explore and obtain data. The data obtained were then analyzed using the results of interviews and field notes. This case is studied using the theory of evolution by Herbert Spencer. As for the results of this article, in religion there are role models who can intercede for religious people. The presence of religious leaders who become intermediaries for religious people in dealing with world problems. By being religious, humans can increase their own spirituality. The purpose of this study is to find out what the roles of figures are in guiding the community and how the form of leadership of religious leaders affects people's behavior.